Business Ethics in Islamic Perspective: Basic Concepts, Application, and True Success - Samsidar; Kurniadi; Syamsurianto; Muin, Rahmawati; Usman Ali, Sitti Asiqah (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2024)
Ideally, business should be conducted ethically and honestly, as it involves interactions with others. However, in reality, many entrepreneurs engage in fraudulent practices to gain greater profits. This gap has prompted the author to explore how Islam formulates its business concepts. The aim of this research is to explore the basic concepts of Islamic business ethics, analyze the application of these principles in business practice, and determine the indicators of true success from an Islamic perspective. This article is classified as a library research with a qualitative approach. The methodology used is descriptive analysis. The findings reveal that while there is a good understanding of Islamic business ethics principles, their application often lacks consistency with theory, particularly in aspects of social responsibility and spiritual good. The study finds that to achieve true success, businesses must balance worldly profits with social contributions and charitable acts.